Impact of Inherited Prothrombotic Disorders on the Long-Term Clinical Outcome of Percutaneous Transluminal Angioplasty in Patients with Diabetes - Michal Dubský; Alexandra Jirkovská; Libuše Pagáčová; Robert Bém; Andrea Němcová; Vladimíra Fejfarová; Veronika Wosková; Edward B. Jude (Journal of Diabetes Research)
The aim of our study was to analyse inherited thrombotic disorders that influence the long-term outcome of PTA. Methods. Diabetic patients with peripheral arterial disease (PAD) treated by PTA in our centre between 2008 and 2011 were included in the study. Patients were divided into unsuccessful PTA group (75 patients), successful PTA group (58 patients), and control group (65 patients, with diabetes but no PAD). Diagnosis of inherited thrombotic disorders included mutation in factor V (Leiden), factor II (prothrombin), and mutation in genes for methylenetetrahydrofolate reductase—MTHFR (C677T and A1298C). Results. The genotypic frequency of Leiden allele G1691A was significantly associated with a risk of unsuccessful PTA in comparison with successful PTA group and control group (OR 8.8 (1.1–70.6), p=0.041, and OR 9.8 (1.2–79.2), p=0.032, resp.). However, we only observed a trend for the association of the prothrombin allele G20210A and risk of PTA failure. The frequencies of alleles of MTHFR 677 or 1298 did not differ significantly among the groups. Conclusion. Our study showed higher frequency of heterozygous form of Leiden mutation in diabetic patients with unsuccessful outcome of PTA in comparison with patients with successful PTA and diabetic patients without PAD.